CMET-37. CLINICAL UTILITY OF ENCYCLOPEDIC TUMOR ANALYSIS TO TREAT PATIENTS WITH BRAIN METASTASIS IN REFRACTORY CANCERS. (11th November 2019) - Crook, Timothy; Patil, Darshana; Akolkar, Dadasaheb; Ranade, Anantbhushan; Bhatt, Amit; Datta, Vineet; Bhatia, Jatinder; Schuster, Stefan; Patil, Revati; Srinivasan, Ajay; Kathuria, Harjeet; Datar, Rajan
Abstract: Brain metastasis in solid organ cancers is associated with adverse prognosis, which is further aggravated by limited systemic treatment options. Such patients are also often excluded from clinical trials since their poor prognosis is perceived to unfavorably impact trial outcomes and misrepresent efficacy data. We retrospectively evaluated the efficacy of treatment guided by Encyclopedic Tumor Analysis (ETA) in patients with advanced refractory malignancies and brain metastases to determine the impact on outcomes. Freshly biopsied tumor tissue (primary / lymph node / liver) and peripheral blood of patients were used for integrational multi-analyte investigations as part of ETA, which included gene mutations, gene expression, and in vitro chemosensitivity profiling of viable tumor cells. Based on ETA, patients received individualized therapy recommendations. All patients underwent a PET-CT scan as well as MRI scan prior to treatment start to determine extent of disease. All patients underwent follow-up PET-CT scans and brain MRI scans every 6–8 weeks. Of the ten patients with brain metastases, which were evaluated after receiving ETA-guided treatment, the median follow-up duration was 97 days (range 79 – 180 days) during which all ten patients remained progression-free. Median time to progression for these patients on the last (failed) line of treatment was 91 days (range 30 - 176 days). Five patients showed partial response and five patients showed stable disease while on ETA-guided treatment. During the follow-up period, all brain metastases were either stable (n=7) or had regressed (n=3), and none of the patients reported new brain lesions. Personalized ETA guided treatments imparted clinical benefit by halting disease progression in this cohort of high-risk patients who would have otherwise been considered for palliative regimens due to perceived unfavorable prognosis.